Pharmacoeconomic analysis of botulinum toxin in complex therapy for cerebral palsy - A. S. Kolbin; I. A. Vilum; M. A. Proskurin; Yu. E. Balykina (Качественная клиническая практика, 2018)
We have performed the fi rst-ever pharmacoeconomic analysis in a Russian context of botulin toxin drugs as part of combined therapy for juvenile cerebral palsy (JCP) compared to standard clinical practice. Along with health economic modelling, an analysis of “routine clinical practice” was conducted by means of a survey of experts (practicing neurologists). Th ree medical approaches were evaluated: treatment with the use of drug-induced local myorelaxation via Botox® combined with standard clinical practice; treatment with the use of drug-induced local myorelaxation via Dysport® combined with standard clinical practice, and treatment in accordance with standard clinical practice, including rehabilitative and orthopedic care. Markov cycles, probabilistic sensitivity analysis, and budget impact analysis were used for modelling. Th e results show that the use of Botox® combined with standard clinical practice for treatment of focal spasticity in patients with JCP is an economically advantageous medical approach. Th is strategy was characterized by high clinical eff ectiveness with the lowest expenses of the medical approaches compared for treatment of spastic syndrome in JCP patients. As for the budget impact analysis, use of Botox® combined with standard clinical practice would allow saving up to an additional RUB 239 387 964 per 1000 patients with JCP over three years. Th e results of mathematical modelling correspond with information from “typical” clinical practice.